Motor abilities and skill related performance variables: Effect of different training modes on footballers - Syed, I.; Hassanain, M.; Syed, A. A.; Syed, M. A.; Syed, K. A. (Proceedings of the 2016 International Association of Computer Science in Sport (IACSS) Conference, 2016)
The objective of the study was to explore the influence of different training modes on the motor abilities and skill related performance components of footballers. 60 male footballers aged 18 to 25 years were allocated to; Group `A` Continuous running Group `B` fartlek training, Group `C` Interval training and Group `D` control group. All groups trained 3 days per week for 8 weeks for 50 minutes a session. A pre and post-test was obtained on the muscular endurance, flexibility, pulse rate, kicking for distance and dribbling. The results of muscular endurance, flexibility and pulse rate revealed that CRG. FTG and ITG had significantly improved after the training in all the motor components compared with the control group but there were insignificant changes in kicking for distance and dribbling.